Pengembangan Desain Pembelajaran Online terhadap Guru Kelas di Era Pandemik Covid-19 di SD Negeri Jakarta Barat - Damayanti, Dini (ANWARUL, 2022)
The purpose of this study is to identify and obtain information about the impact of the Covid-19 pandemic on the thematic learning process in elementary schools. This research uses a qualitative descriptive approach with a case study method. The setting of the research was carried out at SDN 09 Duri Kosambi West Jakarta. The research subjects included teachers, students, and parents of students by observing and conducting interviews on the implementation of online learning during the COVID- 19 pandemic. The stages of this research follow qualitative research procedures such as data collection, data reduction, data presentation, and drawing conclusions. The results of the study reveal that the implementation of thematic learning cannot be carried out ideally as in normal situations / before the Covid-19 pandemic occurred. More learning is carried out separately and not integrated between subjects as how integrative thematic learning should be carried out. Meanwhile, of the 4 student competencies that should be learning outcomes in thematic learning, the competencies that can be implemented and achieved maximally are knowledge competencies. The results of this study are expected to provide recommendations for education providers and all education stakeholders so that the educational process can continue under any conditions.